Health professionals’ perception of patient safety culture in a university hospital in São Paulo: A cross-sectional study applying the Hospital Survey on Patient Safety Culture - Okuyama, Julia Hiromi Hori; Galvão, Taís Freire; Crozatti, Marcia Terezinha Lonardoni; Silva, Marcus Tolentino (São Paulo Medical Journal, 2019)
BACKGROUND: Patient safety culture is part of the organizational profile of healthcare institutions and is associated with better quality of care. OBJECTIVE: To assess patient safety culture in a university hospital. DESIGN AND SETTING: Hospital-based cross-sectional study conducted in a public university hospital in São Paulo, Brazil, between September and December 2015. METHODS: We randomly selected 68 sectors of the hospital, to include up to 5 employees from each sector, regardless of length of experience. We used the validated Brazilian version of the Hospital Survey on Patient Safety Culture (HSOPS) via an electronic interface. We calculated the percentage of positive responses for each dimension of the HSOPS and explored the differences in age, experience, occupation and educational level of respondents using the chi-square test. RESULTS: Out of 324 invited respondents, 314 (97%) accepted the invitation and were surveyed. The sample presented predominance of women (72%), nursing staff (45%) and employees with less than six years’ experience at the hospital (60%). Nine out of the 12 dimensions showed percentages of positive responses below 50%. The worst results related to “nonpunitive response to errors” (16%). A better safety culture was observed among more experienced staff, nurses and employees with a lower educational level. In the previous year, no events were reported by 65% of the participants. CONCLUSIONS: The patient safety culture presented weaknesses and most of professionals had not re-ported any event in the previous year. A policy for improvement and cyclical assessment is needed to ensure safe care.